Há fundamentalidade nos modelos de VAR fiscal típicos para o Brasil? - Christian Vonbun; Elcyon Caiado Rocha Lima (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The vector autoregressive and structural vector autoregressive (VAR/SVAR) models are the cornerstone of the contemporaneous empirical macroeconomic research, in particular for measuring the impact of fiscal policy shocks. They may be employed as atheoretical models, as well as a mean to support the estimation and to test dynamic stochastic general equilibrium (DSGE) models - the main theoretical tool for modern macroeconomics. Nevertheless, VAR models may be subject to pathologies, such as the non-causality and the non-fundamentalness. They are capable of biasing the estimates in any direction or intensity. The former is related to the existence of explosive roots in the autoregressive polynomials from stationary processes. The latter consists of the non-invertibility of the moving average (MA) representation on the positive powers of the lag operator. Both refer to the insufficiency of the econometrician's data to estimate the model's correct parameters. This study is the first to employ the latest and most efficient tests for non-fundamentalness: the Mario Forni and Luca Gambetti and the Fabio Canova e Mehdi Hamidi Sahneh, in order to test for these pathologies in Brazilian typical fiscal VAR model using contemporary data. The data and model were found to be non-fundamental.
Keywords: C11; C32; C53; E3; E6; E31; H6; 330; fiscal policy; VAR; macroeconometrics; causality; fundamentalness